Har Khet Ko Pani?: Madhya Pradesh’s irrigation reform as a model - Shah, Tushaar; Mishra, G.; Kela, Pankaj; Chinnasamy, Pennan (2016)
The Pradhan Mantri Krishi Sinchayee Yojana programme should concentrate on two low-hanging fruits. First, it should quickly put to use 20-40 million ha of unutilised irrigation potential created in major, medium and minor irrigation projects. Second, it should provide better quality power rations to farmers during the time of peak irrigation demand. Madhya Pradesh has done precisely this and multiplied the state’s irrigated area quickly, at small incremental cost, delivering double-digit agricultural growth.